Altered Norbin Expression in Patients with Epilepsy and a Rat Model. Issue 1 (December 2017) - Xu, Yali; Li, Zengyou; Yao, Li; Zhang, Xingping; Gan, Dan; Jiang, Manchun; Wang, Na; Chen, Guojun; Wang, Xuefeng
Abstract Norbin is widely distributed in neuronal tissues, is a regulator of Ca2+ /calmodulin-dependent protein kinase II (CaMKII) phosphorylation. Norbin is also an important endogenous modulator of metabotropic glutamate receptor 5 (mGluR5) signaling, and nervous system-specific homozygous gene disruptions, result in epileptic seizures. In this study, we aimed to investigate norbin expression patterns in epilepsy and to elucidate the relationships between norbin and mGluR5 and p-CaMKII in epilepsy. Double-immunolabeling, immunohistochemistry and immunoblotting studies showed that norbin was downregulated in the temporal neocortex of patients with temporal lobe epilepsy (TLE) compared with control subjects. Moreover, in a rat model of lithium chloride-pilocarpine-induced epilepsy, norbin expression began to decrease at 6 h after the onset of status epilepticus and remained at a low level until 60 days. In addition, p-CaMKII expression was significantly increased in both patients with TLE and in animal model. Norbin and mGluR5 were found to be co-expressed in neurons of epileptic tissues. Finally, norbin over-expression facilitated by injections of adeno-associated viral vector into the rat hippocampus increased latency and survival in the lithium chloride-pilocarpine model. Thus, our results indicate norbin participates in the pathogenesis of epilepsy, perhaps by modulating mGluR5 signaling, regulating CaMKII phosphorylation, and may exert antiepileptic effects.